Effects of a Multi-Ingredient Oral Supplement on Multiple Object Tracking, Reaction Time, and Reactive Agility - Justine M. Renziehausen; Amy M. Bergquist; Jeffrey R. Stout; Adam J. Wells; David H. Fukuda (Taylor & Francis Group, 2022)
Background The demands of typical daily activities require a constant level of alertness and attention. Multi-ingredient, caffeine-containing supplements have been shown to improve measures of cognitive performance. As many of these supplements become readily available, efficacy of each should be evaluated. Therefore, the purpose of this study is to examine the effects of the 4D dietary supplement on cognition, reaction time, and reactive agility. Methods Seventeen healthy males (n = 8) and females (n = 9) between the ages of 18-40 years old (22.8 ± 2.9 years; 167.3 ± 9.6 cm; 65.4 ± 10.9 kg) participated in this double-blind, randomized crossover study. Participants completed three baseline reaction time assessments on the Dynavision and one baseline multiple object tracking assessment on the Neurotracker. Participants then consumed the oral multi-ingredient supplement containing 150 mg of caffeine or non-caffeinated placebo, mixed with 24 ounces of water, and rested for 45 minutes. Following the rest period, participants completed an additional three reaction time assessments and one multiple object tracking (MOT) assessment, as well as 6-12 trials of the Y-reactive agility test. Repeated measures ANOVAs were used to evaluate YRA performance and change values for Dynavision RT, Dynavision score, and MOT speed with either 4D dietary supplement or placebo. Results A significant time × supplement interaction was shown for MOT speed (p = .040, d = .543). Change scores in MOT speed were significantly different from zero following 4D (mean: 0.224 au; 95% confidence interval: 0.050 to 0.398 au) but not placebo supplementation (mean: −0.046 au; 95% confidence interval: −0.220 to 0.127 au). No time × supplement interaction was shown for Dynavision RT (p = .056, d = −.499) or Dynavision score (p = .093, d = .434). No differences were shown for YRA scores following supplementation for the right side (p = .241, d = −.295) or left side (p = .378, d = −.220). Conclusion The 4D dietary supplement appears to improve measures of cognition, specifically attention/spatial awareness, but not reaction time or reactive agility. Future research should examine the effects of this supplement with a larger, less heterogeneous sample and/or in conjunction with an exercise intervention.